Improving Packaging and Marketing of Local Products Through the Application of Technology and Packaging Innovation to Increase Community Income in Opak Village - Hadi Kurniawanto; Sigit Auliana; Jaka Wijaya Kusuma; Suhandi; Tjahja Muhandri; Nugraha Edhi Suyatma (Universitas Pendidikan Ganesha, 2024)
Community service activities in the national combination program were conducted in Waqf Village, Sukaratu Village, and Majasari Pandeglang District, targeting partner groups of opak food craftsmen and waqf farmer groups. The problem with fostered partners is that no one needs to be able to implement business management, online marketing, or apply innovative technology in standard production processes. Community service in the national service program aims to increase the knowledge and skills of fostered partners in implementing business management, online-based marketing, and technological innovation in the production process. Activity methods include the socialization of national programs, the application of technology in the production process, training, mentoring, and evaluation. The results of this activity show that the two fostered partners can apply business management, online marketing (e-commerce), and the application of packaging technology with nitrogen injection as well as the application of production with solar dome dryers to dry opaque patches, which is very helpful during the rainy season, can still production. There was an increase in the business of the two fostered partners to reach 80%.